An Mosquito Mansonia titillans (Walker) (Insecta: Diptera: Culicidae: Culicinae: Mansoniini) - Diana Rojas-Araya; Derrick Mathias; Nathan Burkett-Cadena (EDIS)
Includes: Introduction – Synonymy- Distribution– Description- Life Cycle and Hosts- Medical Importance – Surveillance and Management - Selected References. Also available on the Featured Creatures website at http://entnemdept.ufl.edu/Creatures/AQUATIC/Mansonia_titillans.htm